A focus review on 3D printing of wearable energy storage devices. Issue 6 (18th May 2022) - Zhu, Yuxuan; Qin, Jiadong; Shi, Ge; Sun, Chuang; Ingram, Malaika; Qian, Shangshu; Lu, Jiong; Zhang, Shanqing; Zhong, Yu Lin
Abstract: Three‐dimensional (3D) printing has gained popularity in a variety of applications, particularly in the manufacture of wearable devices. Aided by the large degree of freedom in customizable fabrication, 3D printing can cater towards the practical requirements of wearable devices in terms of light weight and flexibility. In particular, this focus review aims to cover the important aspect of wearable energy storage devices (WESDs), which is an essential component of most wearable devices. Herein, the topics discussed are the fundamentals of 3D printing inks used, the optimizing strategies in improving the mechanical and electrochemical properties of wearable devices and the recent developments and challenges of wearable electrochemical systems such as batteries and supercapacitors. It can be expected that, with the development of 3D printing technology, realization of the full potential of WESDs and seamless integration into smart devices also needs further in‐depth investigations. Abstract : Advancement of three‐dimensional (3D) printed wearable energy storage devices can be achieved by tuning their mechanical and electrochemical properties through the consideration of ink formulation, the design of pattern and architecture and postprocessing of 3D printed components. The development of printed resolution and seamless integration with the targeted smart wearable devices also needs further in‐depth investigations.